2014
DOI: 10.1002/zoo.21155
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment options for African painted dogs (Lycaon pictus)

Abstract: Best practices for carnivore enrichment encourage the diversity of species-typical behaviors, increased activity, and reduced stereotypic behavior; ideally considering the life-history and behavior of each species. African wild dogs (Lycaon pictus), or painted dogs, are social carnivores that have large home ranges and complex pack dynamics (e.g., variation in group size, relatedness, etc.). As there are relatively few studies on painted dog enrichment, the goal of this study was to compile a list of enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Of the few studies conducted on animal responses to carcass feeding, each has found success with carnivorous mammals (Altman, Gross, & Lowry, 2005;Bond & Lindburg, 1990;Cloutier & Packard, 2014;Mcphee, 2002).…”
Section: What Is the Role Of Carcass Feeding As Enrichment?mentioning
confidence: 99%
See 3 more Smart Citations
“…Of the few studies conducted on animal responses to carcass feeding, each has found success with carnivorous mammals (Altman, Gross, & Lowry, 2005;Bond & Lindburg, 1990;Cloutier & Packard, 2014;Mcphee, 2002).…”
Section: What Is the Role Of Carcass Feeding As Enrichment?mentioning
confidence: 99%
“…While looking across a wide variety of enrichment strategies employed with this species, Cloutier and Packard (2014) were the first to confirm the "perceived success and diversity of options in the food enrichment category" (Discussion, para 1), including the use of carcass feeding. Wild painted dogs could be seen hunting together as often as twice per day and live in very tight-knit packs (Creel & Creel, 1995).…”
Section: What Is the Role Of Carcass Feeding As Enrichment?mentioning
confidence: 99%
See 2 more Smart Citations
“…This relative scarcity of studies represents an area of opportunity for investigating the needs of these animals and successful enrichment strategies for meeting those needs. As another example, Cloutier and Packard (2014), citing a dearth of studies on environmental enrichment for African painted dogs, conducted a survey of institutions participating in the African painted dog Species Survival Plan regarding the types, variety, and implementation of enrichment strategies. Respondents reported a wide variety of enrichment types in use, and the authors noted that individual variation in preferences could be a challenge when interpreting the few available enrichment evaluation studies for application with this species.…”
Section: Focal Speciesmentioning
confidence: 99%